Pengaruh Persepsi Harga, Kualitas Produk, Dan Lokasi Terhadap Keputusan Pembelian Di Warung Sate Madura Cak Kodir - Muhammad Hasbi Fadillah; Prawoto (LPPM Universitas Asa Indonesia, 2022)
This analysis aims to identify the Influence of Price Perception, Product Quality and Location on Purchasing Decisions jointly or partially at Warung Sate Madura cak Kodir. The type of research used is quantitative research with a sample determination technique, namely non-probability sampling in the form of accidental sampling and involving as many as 100 respondents. The technique used is in the form of multiple linear regression. The results of this study show that partially of price perception and location have a significant effect on purchasing decisions, while product quality has no effect and are significant on purchasing decisions. So it is better for the Madura cak kodir satay stalls to improve the quality of their products and maintain aspects of perception of their prices and location